Medical and Health Students’ Acceptance and Perceptions of E-learning During the COVID-19 Lockdowns in the Kingdom of Saudi Arabia: Technology Acceptance Model - Alhur, Anas; Alhur, Arwa; Alhur, Afrah (Journal of Pedagogy and Education Science, 2023)
Many educational institutions around the globe utilise E-Learning, which can provide multiple benefits for learners and teachers. Students have no geographical boundaries to prevent them from learning and receiving many other benefits based on their situation and needs. In this study, we aim to investigate the acceptance and perceptions of e-learning among medical and health students in Saudi Arabia during the COVID-19 lockdown. 99% of the respondents own technologies to access e-learning.  We examined the students' learning types of preferences, and our analysis shows that around 45% preferred e-learning, 32% blended learning, and 23% chose traditional education. 29.3% disagreed, and 22% strongly disagreed that e-learning was easy to use. 32.6% agreed that e-learning was fixable, while 19.5% disagreed. We found that 16% disagreed that e-learning increases the efficiency and effectiveness of their learning, whereas 40% agreed. The researchers assessed respondents' preference for learning methods, and we reported that blended learning was preferable to traditional and e-learning. The current paper confirms the validity of the TAM model in measuring e-learning acceptance and use. We found that Medical and health students have a high favour of using e-learning. However, some issues exist in terms of its easiness.